Ventricular fibrillation due to overdose of loperamide, the "poor man's methadone" - Amr Salama; Yana Levin; Pramod Jha; Richard Alweis (Greater Baltimore Medical Center, 2017)
Loperamide is an over-the-counter antidiarrheal agent that is considered by many patients to be safe, but has been used as a drug of abuse due to its opioid properties. However, cardiotoxicity has been reported, prompting the FDA to release a warning regarding the arrhythmogenic potential of loperamide. We present a case of a 38-year-old female presenting with cardiac arrest thought to be secondary to abuse of the loperamide that she was using to alleviate the heroin withdrawal symptoms. Cardiac ischemia and other drug toxicities were ruled out. Loperamide induces QTc prolongation and cardiac dysrhythmias. She had recurrent ventricular arrhythmias with multiple cardiac arrests. The persistence of the cardiotoxicity for a longer duration than previously reported in the literature is unique in this clinical presentation. We also highlight the potential mechanisms for loperamide cardiotoxicity and its challenging management. Abbreviations: ACLS: Advanced cardiac life support; GI: Gastrointestinal